2015
DOI: 10.1093/carcin/bgv250
|View full text |Cite
|
Sign up to set email alerts
|

Homeostatic responses of colonic LGR5+stem cells following acutein vivoexposure to a genotoxic carcinogen

Abstract: Perturbations in DNA damage, DNA repair, apoptosis and cell proliferation in the base of the crypt where stem cells reside are associated with colorectal cancer (CRC) initiation and progression. Although the transformation of leucine-rich repeat-containing G protein-coupled receptor 5 (Lgr5)(+) cells is an extremely efficient route towards initiating small intestinal adenomas, the role of Lgr5(+) cells in CRC pathogenesis has not been well investigated. Therefore, we further characterized the properties of col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 57 publications
1
14
0
1
Order By: Relevance
“…24 Mice were fed with n-3 PUFA and curcumin alone or in combination for 3 weeks, injected with AOM and analyzed to measure DNA damage (gamma H2AX ( γ H2AX)), apoptosis (terminal deoxynucleotidyl transferase dUTP nick-end labeling (TUNEL)), damage repair (methylguanine-methyl transferase (MGMT)) and proliferation (5-ethynyl-2′-deoxyuridine (EdU)) in crypts 12 and 24 h later as described previously. 4 Because the integration cassette in this mouse model is epigenetically silent in about 60–70% of crypts, 25 we analyzed only GFP-positive crypts using fluorescence microscopy. No differences between GFP high and GFP neg crypts in response to carcinogen and bioactive compounds were observed (data not shown).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…24 Mice were fed with n-3 PUFA and curcumin alone or in combination for 3 weeks, injected with AOM and analyzed to measure DNA damage (gamma H2AX ( γ H2AX)), apoptosis (terminal deoxynucleotidyl transferase dUTP nick-end labeling (TUNEL)), damage repair (methylguanine-methyl transferase (MGMT)) and proliferation (5-ethynyl-2′-deoxyuridine (EdU)) in crypts 12 and 24 h later as described previously. 4 Because the integration cassette in this mouse model is epigenetically silent in about 60–70% of crypts, 25 we analyzed only GFP-positive crypts using fluorescence microscopy. No differences between GFP high and GFP neg crypts in response to carcinogen and bioactive compounds were observed (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…It has been demonstrated that Lgr5 + stem cells are preferentially damaged by AOM in the distal colon compared with differentiated cells 4 and n-3 PUFA reduce AOM-induced DNA adducts, 26 which cause double-strand breaks (DSBs). 4 Therefore, to determine the chemoprotective effects of combinatorial bioactives on AOM-induced DNA damage in Lgr5 + stem cells as compared with differentiated cells in vivo , we measured γ H2AX, a marker of the double-strand breaks.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This response has been demonstrated with other carcinogens that stimulate apoptotic removal of DNA damaged cells, which occurs throughout the crypt, including at the base of the crypt where the adult colon stem cells reside. [41][42][43] Wang et al 40 followed up this experiment using the same design in which they discovered that expression of select genes (e.g., NADPH oxidase, Nox) is elevated. They also noted that downregulation of Nox expression reduced cell cycle activity and allowed apoptosis to occur.…”
Section: Cooking Effects On Pro-mutagenic Compoundsmentioning
confidence: 99%